2012
DOI: 10.3762/bjnano.3.101
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of oligo- and polythiophenes modified by substituents

Abstract: SummaryThe electronic and structural properties of oligo- and polythiophenes that can be used as building blocks for molecular electronic devices have been studied by using periodic density functional theory calculations. We have in particular focused on the effect of substituents on the electronic structure of thiophenes. Whereas singly bonded substituents, such as methyl, amino or nitro groups, change the electronic properties of thiophene monomers and dimers, they hardly influence the band gap of polythioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
6
39
0
Order By: Relevance
“…Nevertheless, the spectra of the monomers of both polymers have shown a good match with the experimentally measured spectra ( figure 7). Interestingly, these results are supported by the previous study that studied the impact of extended conjugation on a substituted and non-substituted oligo-and polythiophenes [34]. One of the significant outcomes from this study has concluded that the width of the HOMO-LUMO gap (band gap) decreases with increasing size of the oligomer and the inclusion of electron-donating substituent.…”
Section: Effect Of the Length Of Conjugation On The Band Gapsupporting
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, the spectra of the monomers of both polymers have shown a good match with the experimentally measured spectra ( figure 7). Interestingly, these results are supported by the previous study that studied the impact of extended conjugation on a substituted and non-substituted oligo-and polythiophenes [34]. One of the significant outcomes from this study has concluded that the width of the HOMO-LUMO gap (band gap) decreases with increasing size of the oligomer and the inclusion of electron-donating substituent.…”
Section: Effect Of the Length Of Conjugation On The Band Gapsupporting
confidence: 79%
“…This difference can be accredited to the inclusion of the OH-substituent in the polymer chain (figure 8). The presence of the OH-substituent leads to a significant change on the electronic structure of the polymer due the electrondelocalization (resonance effect) and lower the band gap [34,35]. …”
Section: Dft Calculations Resultsmentioning
confidence: 99%
“…The electronic properties of a material is governed by the band gap and therefore it is essential to successfully design such oligomers and polymers to understand the changes in band gap of conjugated oligomers or polymers with respect to their chemical structure. Recently Rittmeyer and Grob [10] have studied the effect of substituents on polythiophenes (PT) and reported that the electronic properties of PTs are unaltered by strongly bonded substituents except for the phenyl group. Chou et al [11] investigated PTs and found that the band gaps are decreased with electron donating substituents and increased with electron withdrawing substituents.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the modeling of a liquid requires the determination of free energies instead of just total energies, which means that computationally expensive statistical averages have to be performed in order to evaluate free-energy differences. Although electronic structure calculations based on density functional theory can reproduce the properties of planar arrangements of aromatic molecules satisfactorily [1518], the large size of the considered systems and the requirement to perform thermal averages make first-principles electronic-structure calculations computationally prohibitively expensive. Therefore we employed classical force fields as included in the Forcite module of the Accelrys’ Materials Studio package to describe the interaction between adsorbate, substrate and solvent.…”
Section: Introductionmentioning
confidence: 99%